Long-term prevention of bladder cancer progression by alpha1-oleate alone or in combination with chemotherapy - Hien, Tran Thi; Ambite, Ines; Wan, Murphy Lam Yim; Cavalera, Michele; Esmaeili, Parisa; Chaudhuri, Arunima; Sabari, Samudra; Babjuk, Marek; Svanborg, Catharina (International journal of cancer, 2023)
Bladder cancer is common and one of the most costly cancer forms, due to a lack of curative therapies. Recently, clinical safety and efficacy of the alpha1-oleate complex was demonstrated in a placebo-controlled study of nonmuscle invasive bladder cancer. Our study investigated if long-term therapeutic efficacy is improved by repeated treatment cycles and by combining alpha1-oleate with low-dose chemotherapy. Rapidly growing bladder tumors were treated by intravesical instillation of alpha1-oleate, Epirubicin or Mitomycin C alone or in combination. One treatment cycle arrested tumor growth, with a protective effect lasting at least 4 weeks in mice receiving 8.5 mM of alpha1-oleate alone or 1.7 mM of alpha-oleate combined with Epirubicin or Mitomycin C. Repeated treatment cycles extended protection, defined by a lack of bladder pathology and a virtual absence of bladder cancer-specific gene expression. Synergy with Epirubicin was detected at the lower alpha1-oleate concentration and in vitro, alpha1-oleate was shown to enhance the uptake and nuclear translocation of Epirubicin, by tumor cells. Effects at the chromatin level affecting cell proliferation were further suggested by reduced BrdU incorporation. In addition, alpha1-oleate triggered DNA fragmentation, defined by the TUNEL assay. The results suggest that bladder cancer development may be prevented long-term in the murine model, by alpha1-oleate alone or in combination with low-dose Epirubicin. In addition, the combination of alpha1-oleate and Epirubicin reduced the size of established tumors. Exploring these potent preventive and therapeutic effects will be of immediate interest in patients with bladder cancer.
Keywords: nádory močového měchýře; Mitomycin; myši; močový měchýř; epirubicin; Neoplasm Recurrence, Local; Oleic Acid; Animals; Urinary Bladder Neoplasms; Mice; Epirubicin; protinádorová antibiotika; Antibiotics, Antineoplastic; lokální recidiva nádoru; Urinary Bladder; zvířata; mitomycin; kyselina olejová